2010
DOI: 10.1007/s00253-010-3001-9
|View full text |Cite
|
Sign up to set email alerts
|

Modification of yeast characteristics by soy peptides: cultivation with soy peptides represses the formation of lipid bodies

Abstract: We have previously reported that the cultivation of yeast cells with soy peptides can improve the tolerance of yeast to freeze-thaw stress (Izawa et al. Appl Microbiol Biotechnol 75:533-538, 2007), indicating that soy peptides can modify the characteristics of yeast cells. To gain a greater understanding of the potencies of soy peptides, we further investigated the effects of cultivation with soy peptides on yeast physiology and found that soy peptides repress the formation of lipid bodies (also called lipid d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…Moreover, hydrolyzed casein (and not the intact protein) was found to possess hypolipidemic activities in obese-prone male C57BL/6J mice [16]. Furthermore, soy peptides decreased TG accumulation in yeast through the downregulation of lipogenic DGA1 mRNA compared to treatments with proteins or amino acid mixture of similar amino acid composition [17]. These findings support the direct hypolipidemic effects of food protein-derived peptides.…”
Section: Dietary Peptides and Hyperlipidemiamentioning
confidence: 89%
“…Moreover, hydrolyzed casein (and not the intact protein) was found to possess hypolipidemic activities in obese-prone male C57BL/6J mice [16]. Furthermore, soy peptides decreased TG accumulation in yeast through the downregulation of lipogenic DGA1 mRNA compared to treatments with proteins or amino acid mixture of similar amino acid composition [17]. These findings support the direct hypolipidemic effects of food protein-derived peptides.…”
Section: Dietary Peptides and Hyperlipidemiamentioning
confidence: 89%
“…Moreover, various physiological functions of soy peptides on microorganism cells have also been reported. Cultivation of yeast cells in medium containing soy peptides could improve the tolerance to freeze–thaw stress of baker's yeast, repress the formation of lipid bodies and accelerate alcoholic fermentation of brewer's yeast (Izawa et al ., ; Kitagawa et al ., ; Ikeda et al ., ). All these findings indicated that soy peptides can modify the characteristics of brewer's yeast.…”
Section: Introductionmentioning
confidence: 97%
“…For example, soy peptides, the proteolytic products of soy proteins, can reduce serum lipid levels, scavenge free radicals, and reduce oxidative stress in mammalian cells (6)(7)(8). In yeast, soy peptides improve tolerance to freeze-thaw stress, repress the formation of lipid bodies (9), and accelerate ethanol fermentation (10,11). hPepT1 and hPepT2 are human peptide transporters expressed in the small intestine and the kidney, respectively (12).…”
mentioning
confidence: 99%